Coronary Artery By-Pass Grafting in Patient With Paroxysmal Nocturnal Hemoglobinuria (Case Report) - A. Amendola; G. Paternoster; S. P Pascale; R. Nuccorini; M. D'Amora; G. Pittella; R. D'Ascoli; F. Prestipino; G. Luzi; M. Pizzuti (Общая реаниматология, 2021)
Paroxysmal nocturnal haemoglobinuria (PNH) is a clonal haematopoietic stem cell disease that presents with haemolytic anaemia, thrombosis and bone marrow failure. We report a case of a 51-year-old male with a history of PNH in treatment with Eculizumab admitted to our Hospital for acute chest pain and dyspnoea. The diagnosis was a triple vessel disease and patient was scheduled for coronary artery bypass grafting surgery. To balance the risk between thrombosis and bleeding in this particular clinical setting, we decided to use thromboelastography (TEG) as point of care solution and we used the R parameter as the target of our anticoagulant therapy. The R parameter between 11 and 14 sec can be used as a target value to balance the risk; in addition, there was no evidence of acute hemolysis during the surgery and supplemental dose of Eculizumab was administered in order to minimize any potential exacerbation of intravascular hemolysis.